Bioclimatic strategies in the evaluation of thermal performance in low cost housing in Sinop – MT - Marafon, Cristiane; Laco, Mirian; Sanches, João Carlos Machado; Leão, Marlon; Leão, Érika Fernanda Toledo Borges (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This research aims to compare the recommendations proposed by the NBR 15220 and by the Fuzzy Mahoney’s Method with what has been implemented in Sinop/MT and, thereby, verify the reach of the bioclimatic strategies in social housing projects in this city. The adopted methodology consisted of verifying the characteristics related to the dimensions and the materials employed in low cost housing executed in the city. For this, three units of residential buildings single-family from three different housing constructions were objects of study. The results demonstrate that these units are not executed with a view to thermal comfort. Only one of the recommendations contained in the methods adopted was fully met, in only two of the three residences evaluated. There is a clear need for adoption of wider openings in the buildings, better orientation and distribution of land occupation, besides the increase of green areas in them.